Human Immunodeficiency Virus Type 1 Nef: Adapting to Intracellular Trafficking Pathways - Roeth, Jeremiah F. (American Society for Microbiology, 2006)
The Nef protein of primate lentiviruses is a unique protein that has evolved in several ways to manipulate the biology of an infected cell to support viral replication, immune evasion, pathogenesis, and viral spread. Nef is a small (25- to 34-kDa), myristoylated protein that binds to a collection of cellular factors and acts as an adaptor to generate novel protein interactions to accomplish specific functions. Of the many biological activities attributed to Nef, the reduction of surface levels of the viral receptor (CD4) and antigen-presenting molecules (major histocompatibility complex class I) has been intensely examined; recent evidence demonstrates that Nef utilizes multiple, distinct pathways to affect these proteins. To accomplish this, Nef promotes the formation of multiprotein complexes, recruiting host adaptor proteins to commandeer intracellular vesicular trafficking routes. The altered trafficking of several other host molecules has also been reported, and an emerging theory suggests that Nef generates pleiotrophic effects in the secretory and endocytic pathways that reprogram intracellular protein trafficking and may ultimately provide an efficient platform for viral assembly. This review critically discusses some of the major findings regarding the impact of human immunodeficiency virus type 1 Nef on host protein transport and addresses some emerging directions in this area of human immunodeficiency virus biology.